The #RhodesMustFall and #FeesMustFall student protests through the Kübler-Ross grief model. Issue 4 (4th July 2018) - Konik, I.; Konik, A.
ABSTRACT: This article explores the possibility that the recent #RhodesMustFall and #FeesMustFall student protests at South African universities may be partially underpinned by grief over a dying essentialist assemblage in the wake of the 2012 Marikana massacre – which saw the assemblage severed from the State Apparatus in a way that spelled its doom. Particular focus falls on how the related protests mirror the grief stages identified by Elisabeth Kübler-Ross, and the article concludes by reflecting on possible post-structural curricular interventions that may help to stabilize university operations in the country.